Derivation and Inflection Affixes of English Words in Online News Headlines on Thejakartapost.com Website: A Morphological Study - Dwi Suryani; Agus Hari Wibowo (Universitas Sebelas Maret, 2025)
This study examines the use of derivational and inflectional affixes in English news headlines published on The Jakarta Post website. The morphological analysis method is used to identify the types of affixes used and word formation patterns in the context of online media. The data collection technique was carried out using the observe and note method, where data was obtained by browsing and recording news headlines found on the site. This analysis uses the distribution method with an advanced technique in the form of Direct Element Sharing (BUL). Based on the results of the analysis, 214 words were found, with 60 affixed word data, consisting of 21 words through the derivation process and 39 words through the inflection process. The research findings show that derivational affixes, such as prefixes (